Anglo-Saxon manuscripts : a bibliographical handlist of manuscripts and manuscript fragments written or owned in England up to 1100 - Gneuss, Helmut; Lapidge, Michael, 1942- (Toronto Anglo-Saxon series, 2014)
"Anglo-Saxon Manuscripts is the first publication to list every surviving manuscript or manuscript fragment written in Anglo-Saxon England between the seventh and the eleventh centuries or imported into the country during that time. Each of the 1,291 entries in Helmut Gneuss and Michael Lapidge's Bibliographical Handlist not only details the origins, contents, current location, script, and decoration of the manuscript, but also provides bibliographic entries that list facsimiles, editions, linguistic analyses, and general studies relevant to that manuscript. A general bibliography, designed to provide full details of author-date references cited in the individual entries, includes more than 4,000 items. Compiled by two of the field's greatest living scholars, the Gneuss-Lapidge Bibliographical Handlist stands to become the most important single-volume research tool to appear in the field since Greenfield and Robinson's Bibliography of Publications on Old English Literature."--Publisher's website